VD_FINDINFO HC / 2009 / 119 vom 10. Juli 2009 - VD Tribunal cantonal (2009)
OBLIGATION D'ENTRETIEN, ENFANT, CALCUL, SITUATION FINANCIÈRE | 133 al. 1 CC, 280 al. 2 CC, 285 al. 1 CC, 444 al. 1 ch. 3 CPC